2005
DOI: 10.1080/09513590400021128
|View full text |Cite
|
Sign up to set email alerts
|

Intercycle variabilities of basal antral follicle count and ovarian volume in subfertile women and their relationship to reproductive aging: A prospective study

Abstract: Intercycle variabilities of the antral follicle count and ovarian volume were clinically significant. More variation was observed in the antral follicle count of young infertile patients. Therefore, a low antral follicle count in young, infertile, but ovulatory women should be cautiously interpreted. This may not reflect a low ovarian reserve, and these women may have a high antral follicle count in the next cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
0
18
1
1
Order By: Relevance
“…Changes in the size of the growing follicle cohort responding to exogenous gonadotropins among different menstrual cycles can explain this variation. In a recent study, a significant cycle-to-cycle variation was shown in the AFC, particularly in young infertile women, in a subfertile population (26). Contrarily, our data demonstrated that cycle-to-cycle differences in AFC in repeated cycles of the same patients were not significant in subfertile patients (<40 y of age) and did not appear to influence the predictive capacity of AFC for pregnancy and live birth.…”
Section: Discussioncontrasting
confidence: 36%
“…Changes in the size of the growing follicle cohort responding to exogenous gonadotropins among different menstrual cycles can explain this variation. In a recent study, a significant cycle-to-cycle variation was shown in the AFC, particularly in young infertile women, in a subfertile population (26). Contrarily, our data demonstrated that cycle-to-cycle differences in AFC in repeated cycles of the same patients were not significant in subfertile patients (<40 y of age) and did not appear to influence the predictive capacity of AFC for pregnancy and live birth.…”
Section: Discussioncontrasting
confidence: 36%
“…The mean interval between the two assessments was 5.4 AE 1.2 months. There was no significant difference between the two cycles in the total AFC (16.06 AE 8.9 vs. 15 …”
Section: Resultsmentioning
confidence: 52%
“…Intercycle variability and intraobserver reliability were assessed by calculating limits of agreement, as described by Bland and Altman (19). To compare the cycle variability of different determinants of ovarian reserve, each of which has different scales and units, the ranges between the upper and lower limits of agreement were standardized by expressing them as multiples of the mean (MoM) (15). Multiples of the mean for each variable were calculated by dividing the range between the limits of agreement by its own mean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, first cycle of IVF/ICSI treatment was proposed to be a surrogate ovarian response test (13). Although it has no clinical applicability due to the lack of data from prospective studies, it may be an alternative to overcome disadvantages of variability between ovarian reserve test results (14,15). Optimal gonadotropin starting dose is still a concern and has not been established (16).…”
Section: Discussionmentioning
confidence: 99%